Book of Abstracts of the I International Conference on Night Studies - Garcia Ruiz, M. (2020)
The night has been the subject of multiple readings by the social and human sciences, as well as it has inspired multiple narratives throughout history, literature and popular culture. However, the study of nightlife, practices, and actors only gained attention in recent years. The appearance of “mayors of the night” with the intention of improving urban governance during this period and thus guaranteeing needs, rights and services is the result of a progressive change in the local political paradigm, which begins to face this space-time as a “new” opportunity for its economic, social and cultural development. We could say that the night and the activities that take place in it begin to be projected as forms of tourist attraction, whether for their leisure activities such as discos, parties or other forms of fun; or because of its cultural potential, such as the White Nights. Contemporary urban night implies having active professionals, capable of reacting to any incident, such as the case of health professionals, but also maintaining those professions – often illegal – that tend to be considered problematic or hidden as could be prostitution. Surveillance and control during this period is also a good example of active professions, such as the case of the police, surveillance companies, video-doorman, or firefighters. It has never been so easy to commute in the urban space, public transport normally meets the needs of users, and the emergence of new forms of transport resulting from the circular economy, both of people and goods, completes the demand, not without controversy. The 1st International Conference on Night Studies was an international event that aimed to echo frontier research, artistic works and professional practices related to the study of the urban night in multiple contexts around the world. ICNS is a collaborative effort of the Centre for Research and Studies in Sociology (CIES-IUL), the Interdisciplinary Center of Social Sciences (CICS.NOVA), the Institute of Sociology – University of Porto (ISUP) and the LXNIGHTS Network.